Application of Non-Steroid Anti-Inflammatory Drugs in Chronic Bacterial Prostatitis - Akhmadjanov Furkat Ilyos ugli (Zien Journals, 2023)
Purpose of the study of great importance is the rational choice when using non-steroidal antiinflammatory drugs in the treatment of chronic bacterial prostatitis, determining the effectiveness and ensuring its safety.
Keywords: safety; prostatitis; determining; effectiveness